Potassium fertilization influencing the production and postharvest quality of ‘Paluma’ guava grown under semiarid conditions at Rio Grande do Norte, Brazil - Alencar, Renato Dantas; Leite, Grazianny Andrade; Mendonça, Vander Mendonca; Lima, Franciezer Vicente de; Pereira, Gustavo Alves; Farias, Wagner Cesar de (Comunicata Scientiae, 2016)
The aim of this study was to evaluate the effect of potassium fertilization on yield and final quality of guava fruit variety ‘Paluma’, grown at the Irrigated District of Baixo Açu-RN, Brazil. The experimental was carried out in a completelyrandomized blocks design in split plot with five treatments (0, 0.5, 1.0, 1.5 and 2.0 kg K2O plant-1) with four repetitions. The subplots were composed of two harvest seasons and the following characteristics were evaluated: number of fruits, commercial production, total production, commercial yield, average weight of commercial fruits and average weight of total fruit. For fruit quality the following characteristics were evaluated: vitamin C, soluble solids content, firmness, titratable acidity, flesh pH, fruit length and. With an increasie of K2O dose, a linear increase in the number of fruits was observed and ahigher yield was obtained when a dose of 0.370 kg K2O per plant was applied and a higher fruit firmness was obtained with a dose of 1.2 kg K2O per plant.